Facing the Divine: Busts of Christ in Sixteenth-Century Italy. - LaTores, Alicia. (2017)
Abstract: This thesis examines the early modern viewer reception of sixteenth-century Italian busts of Christ that lack attributes. I determine that the busts were recognizable to the viewer without any elements of identification because Christ's actual physiognomy was believed to be preserved in the True Likenesses. Moreover, this inquiry explores the physical bust form of the sculptures to determine if early modern viewers understood the busts of Christ to be a portrait bust or a reliquary bust. I determine that the busts of Christ have correlations to both types of busts. Thus, the function of the bust is analyzed by comparing the functions and locations of portrait and reliquary busts with the known locations of the busts of Christ. Finally, I posit possible functions for the busts of Christ to understand how early modern Italian viewers may have interacted with the busts.; Thesis (M.A.)--Tufts University, 2011.; Submitted to the Dept. of Art and Art History.; Advisor: Cristelle Baskins.; Committee: Peter Probst, and Marietta Cambareri.; Keywords: Art History, European History, and Religion.